2018
DOI: 10.1126/sciadv.aar5170
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of grain boundaries in graphene through vapor hydrofluoric acid (VHF) exposure

Abstract: Rapid, simple, and large-area imaging of grain boundaries in CVD graphene placed on a SiO2 surface by vapor HF exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
1
34
0
1
Order By: Relevance
“…To limit the resulting exposure time of the double-layer graphene to vapour HF to a few seconds, we carefully timed this etching step. As a result, we did not observe any negative effects of the vapour HF etching on the graphene 56 . Our entire fabrication process is compatible with commercial semiconductor and micro-electromechanical (MEMS) foundry processes and can be implemented once wafer scale graphene transfer evolves from laboratories to fabs 57,58 .…”
Section: Proof Mass Releasementioning
confidence: 58%
“…To limit the resulting exposure time of the double-layer graphene to vapour HF to a few seconds, we carefully timed this etching step. As a result, we did not observe any negative effects of the vapour HF etching on the graphene 56 . Our entire fabrication process is compatible with commercial semiconductor and micro-electromechanical (MEMS) foundry processes and can be implemented once wafer scale graphene transfer evolves from laboratories to fabs 57,58 .…”
Section: Proof Mass Releasementioning
confidence: 58%
“…In this regard, an in‐depth understanding of the formation mechanism of GBs in 2D materials at the atomic scale is crucial to tailor material properties in a controllable way, for example, to eliminate unwanted GBs or to create and exploit specific types of GBs. Recently, significant progress has been made on the formation, atomic structure and properties of GBs in 2D materials, but so far, these works have mainly focused on high‐symmetry 2D materials like graphene, hexagonal boron nitride and transition metal dichalcogenides (TMDs) …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, due to the higher defect density, the local metallic surfaces under the 2D material grain boundaries are susceptible to preferential corrosion. For example, graphene's exposure to vapor hydrofluoric (VHF) acid has shown that VHF preferentially etches the substrate by diffusing through the grain boundaries [120]. Therefore, metal should desirably be coated with monocrystalline in lieu of polycrystalline 2D materials.…”
Section: Defects In 2d Materialsmentioning
confidence: 99%